2019
DOI: 10.1136/archdischild-2018-316309
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of abnormal tone and movement in cerebral palsy

Abstract: BackgroundThe evidence base to guide the pharmacological management of tone and abnormal movements in cerebral palsy (CP) is limited, as is an understanding of routine clinical practice in the UK. We aimed to establish details of motor phenotype and current pharmacological management of a representative cohort across a network of UK tertiary centres.MethodsProspective multicentre review of specialist motor disorder clinics at nine UK centres, collecting data on clinical features and pharmacological management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…A study from the UK of 275 children and young people with cerebral palsy that included all motor types not specific to dystonia found the most commonly used medications for abnormal tone/movement were baclofen, trihexyphenidyl, gabapentin, diazepam and clonidine. Baclofen was often used when both spasticity and dystonia were present whereas trihexyphenidyl, gabapentin and clonidine were all infrequently used if dystonia was not present 7 . The study did not, however, examine combinations of medications nor dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the UK of 275 children and young people with cerebral palsy that included all motor types not specific to dystonia found the most commonly used medications for abnormal tone/movement were baclofen, trihexyphenidyl, gabapentin, diazepam and clonidine. Baclofen was often used when both spasticity and dystonia were present whereas trihexyphenidyl, gabapentin and clonidine were all infrequently used if dystonia was not present 7 . The study did not, however, examine combinations of medications nor dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, Selective Dorsal Rhizotomy may be considered ( 14 ). Dystonia management requires specific medications, including trihexyphenidyl and gabapentin, but current evidence is limited and the majority of care pathways rely on expert opinion ( 66 , 67 ). Choice of treatment should be tailored to the individual and based on their treatment goals.…”
Section: The Nervous Systemmentioning
confidence: 99%
“…The relationship between individualized dosing with ROC, which is generally determined in the operating room in real time based on measurement of neuromotor blockade and titrated up if needed, and the degree of motor involvement in children with spastic CP has not been investigated. Anticonvulsant therapy, which is common in CP due to co-occurring seizure disorders [ 1 , 38 ] has demonstrated an association with altered responsiveness to NMBAs such that some patients on chronic anticonvulsant therapy (CAT) recovered significantly faster from the same single dose of ROC as their control counterparts despite achieving the same level of initial neuromuscular blockade [ 39 ]. A separate study comparing effects of continuous dosing of ROC between patients on CAT and controls, revealed that patients on CAT required higher infusion doses to maintain neuromuscular block resulting in zero twitch response [ 40 ].…”
Section: Introductionmentioning
confidence: 99%